In Vitro And In Vivo Studies Of Cassia Surattensis Flower Against Aspergillus Niger - Vello, Sumathy (2012)
Infectious disease is one of the commonest health problems in developing countries with the rise of antibiotic resistance. Invasive aspergillosis is causing high mortality and morbidity rate among immunosuppressed patients. Therefore, there is an urgent need for novel antifungal therapy to control the fatality rate in the population. Opting on medicinal plants has become the current trend amongst scientific investigators as plants are rich with biological activities. Cassia surattensis flower was studied to identify this organ as a potential antifungal agent. Screening of selected pathogenic microorganisms which were inclusive of Gram positive bacteria, Bacillus subtilis, Bacillus thuringiensis, Micrococcus sp and Staphylococcus aureus, Gram negative bacteria, Escherichia coli, Proteus mirabilis and Salmonella sp and fungi Candida albicans, Aspergillus niger and Rhizopus sp against the flower extract revealed this flower to possess antimicrobial properties. The zone of inhibition for microorganisms from disc diffusion assay ranged from 13 ± 0.04 mm to 18 ± 0.00 mm. Microorganisms that were weak against the flower extract were further evaluated with Minimum Inhibitory Concentration (MIC) assay to determine the flower extract activity against the microorganisms in a dose dependent manner. MIC values for both Gram positive and Gram negative bacteria ranged from 3.125 mg/mL to 25.00 mg/mL. For fungi, the MIC value ranged from 3.125 mg/mL to 6.25 mg/mL. The presence of antifungal agent in the flower extract caused damage to the hyphae and conidiophores of A. niger